PERTANGGUNGJAWABAN HUKUM PELAKU TINDAK PIDANA PERJUDIAN SLOT ONLINE DI INTERNET (STUDI PUTUSAN NO 472/PID.B/2024/PN PSP) - Choirul Amin; Bambang Widarto (YAYASAN PENDIDIKAN DAN PELAYANAN KESEHATAN, 2025)
Fraud is a form of crime classified as an offense against another person's property. It is a criminal act that can be committed by anyone, including members of the Indonesian Army. Fraud committed by a Indonesian Army is considered a serious violation, particularly when they abuse their position for personal gain. This research uses a normative juridical method with a case approach. The regulation of fraud committed by Indonesian Army is stipulated in Article 378 of the Indonesia Penal Code, while the 2023 Penal Code regulates fraud under Article 492. Indonesia Military Penal Code does not specifically regulate fraud, thus members of the Indonesian Army are subject to the general provisions of the Indonesia Penal Code. The criminal liability for fraud committed by a Indonesia Army based on the decision of the Military Court I-04 Palembang Number 7-K/Pm.I-04/Ad/I/2025 resulted in a relatively light sentence of ten months’ imprisonment. Such a lenient sentence, especially for a Indonesian Army, fails to provide a deterrent effect. Judicial decisions should deter criminal acts and help offenders become more responsible individuals who can reintegrate into society as better citizens.